2019
DOI: 10.1097/aln.0000000000002600
|View full text |Cite
|
Sign up to set email alerts
|

Driving Pressure during Thoracic Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Recently, several retrospective studies have suggested that pulmonary complication is related with driving pressure more than any other ventilatory parameter. Thus, the authors compared driving pressure–guided ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 38 publications
5
141
3
1
Order By: Relevance
“…In the DESIGNATION trial, the level of PEEP that results in the lowest ΔP will be identified by the decremental PEEP trial. While in one previous trial of individualized PEEP, an incremental PEEP trial was used to find the best level of PEEP [16], here a decremental PEEP trial is chosen to ascertain that the resulting PEEP sustains the beneficial effects of the RM before the PEEP trial. This cannot be guaranteed when using an incremental PEEP trial, because PEEP is most likely below the closing pressure at start of an incremental PEEP trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the DESIGNATION trial, the level of PEEP that results in the lowest ΔP will be identified by the decremental PEEP trial. While in one previous trial of individualized PEEP, an incremental PEEP trial was used to find the best level of PEEP [16], here a decremental PEEP trial is chosen to ascertain that the resulting PEEP sustains the beneficial effects of the RM before the PEEP trial. This cannot be guaranteed when using an incremental PEEP trial, because PEEP is most likely below the closing pressure at start of an incremental PEEP trial.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the "low PEEP" group receive ventilation with PEEP 5 cm H 2 O. The decision to use a PEEP of 5 cm H 2 O derives from previous trials of intraoperative ventilation [15,16]. PEEP 5 cm H 2 O is the most frequently chosen level in daily practice [1,36]; although there is no absolute consensus on the best level of PEEP, the overall recommendation is to ventilate patients with healthy lungs with this PEEP level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome of the PREP trial is the incidence of PPCs within the first 14 post-operative days. PPCs is defined with the Melbourne Group Scale (MGS) diagnostic scoring tool, which is reliable and valid following thoracic surgery with high inter-rater reliability [35][36][37]. A PPC will be diagnosed when the following four or more factors are identified: 1) new abnormal breath sounds different to pre-operative; 2) chest X-ray findings of atelectasis or consolidation; 3) raised white cell count (WCC) (> 11 × 10 9 /L); 4) temperature > 38°C; 5) purulent sputum differing from preoperative status; 6) signs of infection on sputum culture; 7) pulse oximetry oxygen saturation (SpO 2 ) < 90% without oxygen therapy; and 8) pneumonia diagnosed based on physician's experience [38].…”
Section: Outcome Measures Primary Outcomementioning
confidence: 99%
“…In the P group, VT will be set at 6 ml/kg of predicted body weight combined with individualized PEEP during intraoperative dura mater opening [6,7], but in other periods of general anesthesia, VT will be set at 8 ml/kg of predicted body weight. For the titration method of individualized PEEP [19], VT and respiratory rate will be fixed at 6 ml/kg and 15 beats per minute during PEEP trial. Titration can only begin once the dura is opened.…”
Section: Study Intervention Related Parameter Setting During Operationmentioning
confidence: 99%